An in-depth analysis of factors influencing small-scale cattle farmers’ participation in livestock markets in Western Province of Zambia: navigating challenges and barriers - Mumba, Chisoni; Kasanga, Bertha; Mwamba, Chisanga T.; Sichilima, Timothy; Siankwilimba, Enock; Sitali, Doreen C.; Munkombwe, Joshua; Banda, Reuben; Muma, John Bwalya (Frontiers in Veterinary Science, 2024)
IntroductionsThe low participation of small-scale farmers in livestock markets in sub-Saharan Africa, including Zambia, is a major inhibitor to private sector investment in the livestock subsector. Despite the immense potential of the livestock industry to bolster the economic development of countries in this region, several socioeconomic, environmental, and cultural factors contribute to this hindrance.MethodsThis study was conducted in the Western Province of Zambia and adopted a qualitative research approach to understand the challenges and barriers affecting livestock markets among smallholder cattle farmers. In-depth interviews were conducted with 23 key informants and focus group discussions involving key actors in the dairy and beef value chains. Thematic analysis was employed to analyze the gathered data.ResultsFour themes, including socioeconomic, cultural, market dynamics, and policy and regulatory factors, emerged from this analysis. The sub-themes for socioeconomic factors included access to capital, infrastructure challenges, limited technical knowledge, and inadequate veterinary services. Cultural factors included traditional practices, social norms, and perceptions of livestock, and subthemes for market dynamics included price volatility, lack of market information, and middlemen exploitation. The sub-themes for policy and regulatory factors included policy inconsistencies, land tenure issues, and inadequate government support.ConclusionBy identifying and understanding these factors, policymakers and stakeholders can develop effective and sustainable targeted interventions and policies to encourage smallholder cattle farmers’ participation in the livestock sector.